Konsep Adab Perspektif Al-GhazÄlÄ« Dan Relevansinya Terhadap Pembentukan Karakter - Utomo, Agung Wahyu; Ali, Mohamad; Maksum, Muh. Nur Rochim (Muttaqien, 2023)
This research is motivated by a moral shift among the younger generation, especially students at school, especially in relationships. Many students have bad morals such as like to badmouth their friends, like to prank friends and behave impolitely towards teachers and parents. This study aims to describe the etiquette of association and friendship according to al-GhazÄlÄ«'s BidÄyatul HidÄyah book and identify the relevance of social and friendship etiquette according to al-GhazÄlÄ«'s BidÄyatul HidÄyah book on the formation of student character. This type of research is a type of library research with qualitative research and data analysis using content analysis with a descriptive approach. Â The results of this study conclude that the concepts of etiquette of al-GhazÄlÄ«'s perspective and its relevance to character building is: 1). Etiquette to students, setting a good example to students; 2). Etiquette to the teacher, respect him by greeting first when you meet him; 3) Etiquette to Parents, Doing good and respecting them, without having to be asked by them first; 4). Etiquette to others, Always close and don't spread the disgrace of your friends